If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -5 = (3m + 5) Reorder the terms: -5 + 8m = (3m + 5) Reorder the terms: -5 + 8m = (5 + 3m) Remove parenthesis around (5 + 3m) -5 + 8m = 5 + 3m Solving -5 + 8m = 5 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -5 + 8m + -3m = 5 + 3m + -3m Combine like terms: 8m + -3m = 5m -5 + 5m = 5 + 3m + -3m Combine like terms: 3m + -3m = 0 -5 + 5m = 5 + 0 -5 + 5m = 5 Add '5' to each side of the equation. -5 + 5 + 5m = 5 + 5 Combine like terms: -5 + 5 = 0 0 + 5m = 5 + 5 5m = 5 + 5 Combine like terms: 5 + 5 = 10 5m = 10 Divide each side by '5'. m = 2 Simplifying m = 2
| 3.45(4)-8.18(1)= | | 3+3*6+2=-17 | | 500*98+x*0=(500+x)*30 | | 6n+3-5=-1 | | 6y+814=1186 | | cos(20)=(9/x) | | 32/-7 | | 4(1/4) | | 3x+10y=-15 | | F^2-22f+72=0 | | (5-8w)(5+8w)= | | 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 | | 5x-7=4x-7 | | x/9-9=9 | | 9-(5a+1)+3a+7= | | -8h-6h=24 | | 4^3(8^(1/3)z^2 |